Androgen receptor-modulatory microRNAs provide insight into therapy resistance and therapeutic targets in advanced prostate cancer - Fletcher,C; Sulpice,E; Combe,S; Shibakawa,A; Leach,D; Hamilton,MP; Chrysostomou,SL; Sharp,A; Welti,J; Yuan,W; Dart,D; Knight,E; et al. (Oncogene, 2019)
Androgen receptor (AR) signalling is a key prostate cancer (PC) driver, even inadvanced ‘castrate-resistant’ disease (CRPC). To systematically identify microRNAs (miRs) modulating AR activity in lethal disease, hormone-responsive and -resistant PC cells expressing a luciferase-based AR reporter were transfected with a miR inhibitor library; 78 inhibitors significantly altered AR activity. Upon validation, miR-346, miR-361-3p and miR-197 inhibitors dramatically reduced AR transcriptional activity, mRNA and protein levels, increased apoptosis, reduced proliferation, repressed EMT, inhibited PC migration and invasion, demonstrating additive effects with AR inhibition. Corresponding miRs increased AR activity through a novel and anti-dogmatic mechanism of direct association with AR 6.9kb 3’UTR and transcript stabilisation. In addition, miR-346 and miR-361-3p modulation altered levels of constitutively-active AR variants, and inhibited variant-driven PC cell proliferation, so may contribute to persistent AR signalling in CRPC in the absence of circulating androgens. Pathway analysis of AGO-PAR-CLIP-identified miR targets revealed roles in DNA replication and repair, cell cycle, signal transduction and immune function. Silencing these targets, including tumour suppressors ARHGDIA and TAGLN2, phenocopied miR effects, demonstrating physiological relevance. MiR-346 additionally upregulated the oncogene, YWHAZ, which correlated with grade, biochemical relapse and metastasis in patients. These AR-modulatory miRs and targets correlated with AR activity in patient biopsies, and were elevated in response to long-term enzalutamide treatment of patient-derived CRPC xenografts. In summary, we identified miRs that modulate AR activity in PC and CRPC, via novel mechanisms, and may represent novel PC the